The evaluation of pain in amyotrophic lateral sclerosis: A case controlled observational study. Issue 7 (December 2014) - Wallace, Victoria C. J.; Ellis, Cathy M.; Burman, Rachel; Knights, Catherine; Shaw, Christopher E.; Al-Chalabi, Ammar
Abstract Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder leading to progressive paralysis. ALS is complicated by a number of non-motor symptoms including pain. Pain in ALS has been poorly studied and poorly managed. This study aimed to collate information regarding pain in ALS using standardized pain questionnaires. Forty-two patients with ALS participated in the study. Control subjects included 41 age-matched healthy volunteers and 42 age-matched patients with neurological conditions other than ALS. Data on pain were collected using the The Brief Pain Inventory and The painDetect Questionnaire. Eighty-five percent of subjects with ALS reported pain versus 50% of neurology clinic controls and 35% of healthy controls (p < 0.01). Pain in ALS included cramping, aching, tiring, sharp and tender, and was non-neuropathic. Pain impacted significantly on mood, general activity, relationships and general enjoyment of life. Fifty-four percent of people with painful ALS used regular analgesia and 29% regular opioids. Other non-motor symptoms suffered included tiredness, constipation, urinary problems, itching and drowsiness. In conclusion, these data support the fact that pain is a significant symptom in ALS which impacts on quality of life. These data can be used to educate clinicians and patients to promote better multidisciplinary management of ALS symptoms and a better quality of life.